Genetic susceptibility factors in familial nasopharyngeal carcinoma - Kaderi, Mohd Arifin; Purnomosari, Dewajani; Gaborieau, Valerie; Voegele, Catherine; Forey, Nathalie; Durand, Geoffroy; Chabrier, Amelie; Michelon, Jocelyne; Calvez - Kelm, Florence Le; Lesueur, Fabienne; Carrington, Mary; Hildesheim, Allan; et al. (3d PABCS, 2016)
Nasopharyngeal carcinoma is common in Southern China, Hong Kong, Taiwan and Southeast Asian countries. The current study was performed on an exceptionally large multiplex NPC family from Sarawak, Malaysia (denoted as JAQBAB family). We aimed to explore the segregation of deleterious mutation(s) or NPC risk- associated allele within the genomic segment shared identical by descent (IBD) between the affected individuals. Genome-wide SNP-array covering all somatic chromosomes were performed on 11 of the NPC patients and their first-degree family members. The kinship was assessed and pairwise IBD estimation between target individuals were performed. Haplotype phasing was also performed on certain region of interests. Whole-exome sequencing was performed to identify deleterious mutations. The highest IBD score was detected within chromosome 10. Analysis of the exome sequencing data, however, did not find any deleterious mutation within this region that was shared between individuals in the JAQBAB family. Highest IBD score at chromosome 6 was found within the major histocompatibility complex (MHC) region, supporting strong HLA-EBV-NPC association that has been reported in an earlier study. HLA deep sequence-based typing (SBT) and gene sequencing on the 11 NPC patient samples revealed that the segregation of HLA-A*27:07 allele was consistent with the haplotype phasing pattern. Our results suggest that HLA-A*24:07 may harbour the risk allele for NPC among the subjects. However, further analysis is required before any definitive conclusion can be made. Further studies on the HLA-A*24:07 sequence may reveal more specific variation within this gene that can be associated with NPC risk in this family. In addition, further studies on HLA-A and risk of NPC other Southeast-Asian populations may shed more understanding about the association between HLA-A*24:07 and sporadic NPC in this region of the world.